GIS-based mapping of flashflood susceptible areas in Bukang Liwayway, Kibawe, Bukidnon - Ackerlund, George; Olpenda, Alex S.; Puno, Rena Christina C.; Lacandula, Laarni F.; Maghuyop, Ida V.; Villar, Ricardo G. (2022)
This study aimed to generate a GIS-based flashflood hazard susceptibility map using the geographical information system (GIS) and frequency ratio (FR) techniques in one of the geographically isolated and disadvantaged areas (GIDAs) of the country, which is the barangay Bukang Liwayway of Kibawe, Bukidnon. There are 160 sample points conducted for flashflood inventory to calculate FR and the flashflood prediction weights values needed to generate the flashflood susceptibility map. The elevation, slope, aspect, curvature, topographic wetness index, drainage density, LULC, normalized difference vegetation index, and rainfall are the nine controlling factors that are selected. Results show that the areas exposed to flashflood with low, medium, and high-risk levels of susceptibility consist of 89.8, 4.4, and 5.7% of the total land, respectively, with 25 households exposed to high risk. The study determined the possible site for the evacuation center based on the spatial analysis resulting in the overlaying of different thematic map layers based on flashflood susceptibility factors. The study emphasizes the integration of the findings in the localized comprehensive land-use plan to realize the challenge of building a sustainable and hazard-resilient human community in Bukang Liwayway.
Keywords: Floods; Geographic Information Systems